Peran Pendidikan dalam Membentuk Pemimpin Bangsa Berkarakter - Tukhas Shilul Imaroh (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
Indonesia is a large and wealthy nations, also has been a chance to advance and compete globally. Every nation has been its problems and challenges to compete and thrive. As an authorized capital ahead and compete globally needed revitalization and strengthening of the character and quality of human resources with a strong leader. Indonesian nation requires a strong leader and a character that is a leader who conscience underlying the use of thinking, attitudes and behavior, as well as thrust and high fighting spirit to realize the virtues it stands for. The character of a leader is reflected in the accumulation of speech, thoughts, and actions to be consistent pattern in the long period. The leader of that character can be realized through character education. Educationis the corner stone for shaping personality. Education was not always come from formal education such as high school or college. Informal and non-formal education also has a similar role to shape the personality.